Respuesta :
Answer:
[tex]\huge\boxed{ f^{-1}(x) = \sqrt[3]{-x-9}}[/tex]
Step-by-step explanation:
[tex]f(x) = -x^3-9[/tex]
Put f(x) = y
[tex]y = -x^3-9[/tex]
Interchange x and y
[tex]x = -y^3-9[/tex]
Solve for y
[tex]x = -y^3-9[/tex]
Add 9 to both sides
[tex]-y^3 = x+9[/tex]
Divide both sides by -1
[tex]y^3 = -x-9[/tex]
Take cube root to both sides
[tex]y = \sqrt[3]{-x-9}[/tex]
Put [tex]y = f^{-1}(x)[/tex]
[tex]\boxed{f^{-1}(x) = \sqrt[3]{-x-9}}[/tex]
[tex]\rule[225]{225}{2}[/tex]
Hope this helped!
~AH1807
The inverse function of the given function is [tex]f^{-1} (x)[/tex]=∛-x-9.
The given function is f(x)=-x³-9.
How to find the inverse function?
To find the inverse of a function, write the function y as a function of x i.e. y = f(x) and then solve for x as a function of y.
Now, replace f(x)=y.
y=-x³-9
Interchange the variables.
That is, x=-y³-9
Solve for y.
That is, y³=-x-9
⇒y=∛-x-9
Solve for y and replace with [tex]f^{-1} (x)[/tex].
[tex]f^{-1} (x)[/tex]=∛-x-9.
Therefore, the inverse function of the given function is [tex]f^{-1} (x)[/tex]=∛-x-9.
To learn more about the inverse function visit:
https://brainly.com/question/2541698.
#SPJ2